Learning curve of left bundle branch area pacing with standard stylet-driven pacing leads: a single center prospective observational study in Korea. (19th May 2022) - Yu, G; Kim, TH; Yu, HT; Joung, BY; Pak, HN; Lee, MH
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Although cardiac pacing is an essential therapy for bradycardia, conventional right ventricular pacing (CRVP) can cause electrical-mechanical dyssynchrony. Left Bundle Branch Area Pacing (LBBAP) is a new conduction system pacing strategy that includes a normal conduction system and therefore maintains synchronous ventricular contraction. Most of the experience with LBBAP is done in a lumen‐less lead with fixed helix design, and this device is not available in sometimes. Purpose: This study aimed to evaluate the learning curve of LBBAP using standard stylet-driven lead with extendable helix design. Methods: This study enrolled patients who underwent permanent cardiac pacemaker implantation at a University Hospital in South Korea from December 2020 to October 2021. LBBAP was performed with a 5.6Fr stylet‐driven pacing lead with an extendable helix. The learning curve was assessed by analyzing fluoroscopy time and procedure time. Results: In 65 patients who underwent LBBAP during the observation period, mean fluoroscopy time and procedural time were 17.1 ± 17.2 minutes and 64.2 ± 33.5 minutes, respectively in this study. The learning curve for achieving LBBAP appears to plateau after around 24th case with a progressive reduction in procedure time. This is a significantly shorter period of time when compared to the previously reported learning curves of his bundle pacing (30-50cases), previously developed conduction system pacing strategy. Conclusion: During initial experience with LBBAP, fluoroscopy and procedural time continue to improve with operator experience. For physicians who are experienced at cardiac pacemaker implantation, the steepest part of the learning curve of LBBAP appears to be over the first 20-25 cases.